2020
DOI: 10.1074/jbc.ra120.014976
|View full text |Cite
|
Sign up to set email alerts
|

PDLIM5 inhibits STUB1-mediated degradation of SMAD3 and promotes the migration and invasion of lung cancer cells

Abstract: Transforming growth factor β (TGFβ) signaling plays an important role in regulating tumor malignancy, including in non-small cell lung cancer (NSCLC). The major biological responses of TGFβ signaling are determined by the effector proteins SMAD2 and SMAD3. However, the regulators of TGFβ-SMADs signaling are not completely revealed yet. Here, we showed that the scaffolding protein PDZ and LIM domain protein 5 (PDLIM5, ENH) critically promotes TGFβ signaling by maintaining SMAD3 stability in NSCLC. Firstly, PDLI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…In NSCLC, TGF-β signaling is frequently enhanced and promotes EMT and tumor metastasis, whereas SMAD3 inhibition diminished TGF-β-induced EMT in cancer cells [ 29 ]. In addition, SMAD3 overexpression was demonstrated to accelerate TGF-β-mediated NSCLC metastasis [ 30 ]. In this work, the oncogenic role of SMAD3 in NSCLC via activating RAB26 expression was uncovered.…”
Section: Discussionmentioning
confidence: 99%
“…In NSCLC, TGF-β signaling is frequently enhanced and promotes EMT and tumor metastasis, whereas SMAD3 inhibition diminished TGF-β-induced EMT in cancer cells [ 29 ]. In addition, SMAD3 overexpression was demonstrated to accelerate TGF-β-mediated NSCLC metastasis [ 30 ]. In this work, the oncogenic role of SMAD3 in NSCLC via activating RAB26 expression was uncovered.…”
Section: Discussionmentioning
confidence: 99%
“…The PDLIM5 gene is a protein that binds to several proteins, such as PKC, PKA, PKD, and AMPK, and is important in signal modulation pathways [ 18 ]. In our study, rs12500426 was associated with higher mortality and incidence, being more frequent in Africans.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has demonstrated that PDLIMs are dysregulated in variety of tumors and are involved in various cellular and intercellular processes. For instance, PDLIM1 knockdown induces EMT and promotes invasion and metastasis in hepatocellular carcinoma (HCC) cells [ 36 ]; overexpression of PDLIM2 and PDLIM7 could serve as adverse prognostic factors for acute myeloid leukemia [ 37 ]; downregulation of PDLIM4 is correlated with aggressive tumor growth and poor prognosis in ovarian cancer patients [ 38 ]; PDLIM5 knockdown inhibited TGF β -signaling and TGF β -induced epithelial-mesenchymal transition [ 39 ]. However, to date, the association between PDLIM expression and clinicopathological features and prognosis of PRAD has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%